Emotional self-regulation, virtual reality and neurofeedback - Pinheiro, Joana (2021)
The most common mental problems are anxiety disorders, affecting today about 264 million people in the world. The reference treatments present limitations, such as their side effects and long intervention periods. Recently, various approaches have emerged, such as neurofeedback, virtual reality and serious games.